2014
DOI: 10.2203/dose-response.14-032.agrawal
|View full text |Cite
|
Sign up to set email alerts
|

Pre-Conditioning with Low-Level Laser (Light) Therapy: Light before the Storm

Abstract: h Pre-conditioning by ischemia, hyperthermia, hypothermia, hyperbaric oxygen (and numerous other modalities) is a rapidly growing area of investigation that is used in pathological conditions where tissue damage may be expected. The damage caused by surgery, heart attack, or stroke can be mitigated by pre-treating the local or distant tissue with low levels of a stress-inducing stimulus, that can induce a protective response against subsequent major damage. Low-level laser (light) therapy (LLLT) has been used … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
48
0
8

Year Published

2015
2015
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(57 citation statements)
references
References 127 publications
1
48
0
8
Order By: Relevance
“…[40][41][42] Some of these benefits could potentially aid in the reversal of renal fibrosis, a condition in which restoration of normal epithelium, endothelium, and the reduction of ongoing inflammation could impact progression to endorgan failure. In our proof of concept study, we observed that each wavelength had slightly different effects on the features of renal fibrosis, which could be categorized as mitigating mechanisms of fibrosis (apoptosis, TGF-beta production) or enhancing mechanisms of regeneration (mitochondrial activation, proliferation).…”
Section: Discussionmentioning
confidence: 99%
“…[40][41][42] Some of these benefits could potentially aid in the reversal of renal fibrosis, a condition in which restoration of normal epithelium, endothelium, and the reduction of ongoing inflammation could impact progression to endorgan failure. In our proof of concept study, we observed that each wavelength had slightly different effects on the features of renal fibrosis, which could be categorized as mitigating mechanisms of fibrosis (apoptosis, TGF-beta production) or enhancing mechanisms of regeneration (mitochondrial activation, proliferation).…”
Section: Discussionmentioning
confidence: 99%
“…Em nível celular, a radiação eletromagnética é absorvida pelo citrocromo c oxidase (COX), situado na mitocôndria celular (unidade IV na cadeia respiratória mitocondrial). A absorção dos fótons pelo COX favorece o fluxo de transferência de elétrons na cadeia mitocondrial, proporcionando aumento da síntese de Adenosina trifosfato (ATP), Óxido Nitroso e do metabolismo celular, resultando em efeitos bioquímicos e terapêuticos (AGRAWAL et al, 2014) Os efeitos da TLBI podem ser empregados no tratamento da HZ facial e da NPHT em todas as fases. Na fase prodrômica, a TLBI pode ser utilizada para diminuição da dor e para aumentar a resposta imunológica contra vírus da varicelazóster.…”
Section: Resultsunclassified
“…Esses mecanismos favorecem a aceleração de processos metabólicos e a troca de nutrientes, na qual propicia a ação das células de defesa (PINHEIRO; BRUGNERA JÚNIOR; ZANIN, 2010;GARCEZ;RIBEIRO;NÚÑEZ, 2012;AGRAWAL et al, 2014).…”
Section: Discussionunclassified
“…3 More recently, it has even been suggested that pre-conditioning where tissue damage may be expected, may be effective in mitigating damage caused by surgery, heart attack, or stroke and possibly to increase athletic performance. 4 In biological tissue the "optical window" where penetration depth is maximized is reportedly from 600nm to 1200nm. 5 Although photobiomodulation is still not a part of mainstream medicine, and the photobiological mechanisms are still a topic of research, therapeutic lasers have primarily used wavelengths in this optical window, to achieve pain relief and tissue regeneration.…”
Section: Laser Therapy Historymentioning
confidence: 99%
“…Photons that are absorbed in cytochrome(c) oxidase increase electron transport, respiration, oxygen consumption and ATP production. 4 Many studies regarding the biostimulation effects of green laser light have been reported. Modifying metabolic activity in rat myocardial cells, while absorption of green band light by fibroblasts lead to DNA synthesis activation.…”
Section: Laser Therapy Mechanismsmentioning
confidence: 99%